Investigation of Forces and Moments during Orthodontic Tooth Intrusion Using Robot Orthodontic Measurement and Simulation System (ROSS) - Corinna L. Seidel; Julian Lipp; Benedikt Dotzer; Mila Janjic Rankovic; Matthias Mertmann; Andrea Wichelhaus; Hisham Sabbagh (Bioengineering, 2023)
The Robot Orthodontic Measurement and Simulation System (ROSS) is a novel biomechanical, dynamic, self-regulating setup for the simulation of tooth movement. The intrusion of the front teeth with forces greater than 0.5 N poses a risk for orthodontic-induced inflammatory root resorption (OIIRR). The aim was to investigate forces and moments during simulated tooth intrusion using ROSS. Five specimens of sixteen unmodified NiTi archwires and seven NiTi archwires with intrusion steps from different manufacturers (Forestadent, Ormco, Dentsply Sirona) with a 0.012″/0.014″/0.016″ wire dimension were tested. Overall, a higher wire dimension correlated with greater intrusive forces Fz (0.012″: 0.561–0.690 N; 0.014″: 0.996–1.321 N; 0.016″: 1.44–2.254 N) and protruding moments Mx (0.012″: −2.65 to −3.922 Nmm; 0.014″: −4.753 to −7.384 Nmm; 0.016″: −5.556 to −11.466 Nmm) during the simulated intrusion of a 1.6 mm-extruded upper incisor. However, the ‘intrusion efficiency’ parameter was greater for smaller wire dimensions. Modification with intrusion steps led to an overcompensation of the intrusion distance; however, it led to a severe increase in Fz and Mx, e.g., the Sentalloy 0.016″ medium (Dentsply Sirona) exerted 2.891 N and −19.437 Nmm. To reduce the risk for OIIRR, 0.014″ NiTi archwires can be applied for initial aligning (without vertical challenges), and intrusion steps for the vertical levelling of extruded teeth should be bent in the initial archwire, i.e., 0.012″ NiTi.